Assessment of Transdermal Vasodilatatory Effect of a Combined Panthenol, Amlodipine, Isosorbide Dinitrate and Betahistine HCl on Peripheral Vessels - Hussein Abdulkadhim A1, Naser A Naser2, Fadhaa A. Ghafil3, Rana Talib Al-Nafakh4, Karrar K. Alhaidar (Institute of Medico-legal Publications Pvt Ltd, 2020)
Peripheral vascular diseases are group of disorders characterized by stenozing peripheral circulation as a complication of primary disease like diabetes mellitus. Peripheral vascular diseases affect 202 million around the world. Peripheral vascular complications of diabetes mellitus are common which affect 30 million over the world and may give rise to infectious necrotizing sequalae called diabetic foot. In a trial of assessment for transdermally applied vasodilator drugs, 30 individual had participated in a case controlled study. Test group (N =11) and control group (N =19) were assessed for the signs of vasodilatation over the dorsum of the hand and figure blood perfusion detection. There was significant increase in perfusion index (from 7 to 11) induced by the test vasodilator as compared with control (from 7 to 8) P <0.05 and parallel results were obtained in induction of redness (redness ratio of 7 with C.I. over 0.95 and thermal increase in degrees of ( C ) over the dorsum of the hand in comparison with the control group. From the overall results the combined vasodilatatory transdermal formula caused a significant peripheral vasodilatation which could be a candidate therapeutic effect in diabetic foot